Confronting the German idealist tradition : Jakob Friedrich Fries, the Friesian School and the Neo-Friesian School /: Jakob Friedrich Fries, the Friesian School and the Neo-Friesian School. (2023) - Ōta, Tadahiro, 1990-
No abstract available